Combined Deep Transverse Friction and Muscle Energy Technique on Mechanical Neck Pain: Article Review - I Putu Mahendra Putra; Made Hendra Satria Nugraha; Ni Wayan Tianing (Physical Therapy Journal of Indonesia, 2020)
Introduction: Since mechanical neck pain has become a common problem, physiotherapists’ role in reducing symptoms caused by mechanical neck pain varies such as muscle energy technique and deep transverse friction. Based on the references, mechanical neck pain defined as a condition non-radicular or local pain which increased pain intensity during movement. The study aims to understand whether deep transverse friction and muscle energy technique are effective to reduce pain the mechanical neck pain.Method: The study used the secondary data through article review which focuses on the journals and articles related to the muscle energy technique and deep transverse friction in the mechanical neck pain. Results: The application and method of muscle energy technique are aimed at normalizing the structure of dysfunctional tissue, such as the shortening of muscles, which indirectly gives a direct effect on the joint. It is suggested as a method to improve the mobility of the joint. Besides, to reduce pain through pain modulation, deep transverse friction was applicable to provide it at the level of the supra-spinal to release endorphins, enkephaline, and cortisol. Conclusion: Either muscle energy technique or deep transverse friction are shown a good effect to reduce pain, neck disability, and increase ROM of the cervical joint in patients with mechanical neck pain. Besides, deep transverse friction has also reducing spasm/tightness at the cervical joint level in patients with mechanical neck pain.